2008
DOI: 10.1016/j.jcrs.2007.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Reducing angiographic cystoid macular edema and blood–aqueous barrier disruption after small-incision phacoemulsification and foldable intraocular lens implantation

Abstract: Diclofenac was more effective than betamethasone in preventing angiographic CME and BAB disruption after small-incision cataract surgery. Thus, nonsteroidal antiinflammatory agents should be considered for routine treatment of eyes having cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 26 publications
0
50
1
1
Order By: Relevance
“…LFP has been used to detect changes in flare levels following various intraocular interventions [54][55][56][57][58][59] and to assess the effect of anti-inflammatory medications on postsurgical inflammation [60][61][62][63][64]. It has been shown that a foldable intraocular lens implantation through a small incision causes less inflammation than a rigid intraocular lens implantation through a larger incision [65].…”
Section: Postsurgical Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…LFP has been used to detect changes in flare levels following various intraocular interventions [54][55][56][57][58][59] and to assess the effect of anti-inflammatory medications on postsurgical inflammation [60][61][62][63][64]. It has been shown that a foldable intraocular lens implantation through a small incision causes less inflammation than a rigid intraocular lens implantation through a larger incision [65].…”
Section: Postsurgical Inflammationmentioning
confidence: 99%
“…LFP studies have shown that topical diclofenac, a nonsteroidal anti-inflammatory drug, is as effective as topical dexamethasone [60][61][62] and more effective than fluorometholone [63] or betamethasone [64] in preventing disruption of blood-aqueous barrier following intraocular surgery.…”
Section: Postsurgical Inflammationmentioning
confidence: 99%
“…31 Pre-operative risk factors include diabetes, uveitis, previous retinal vein occlusion, epitretinal membrane, use of topical prostaglandin analogues and cystoid macular oedema following fellow eye surgery. 32 Studies have shown that use of peri-operative topical non-steroidal anti-inflammatory (NSAID) medication in addition to, or even instead of, routine topical steroid drops, can lower the incidence of pseudophakic angiographic cystoid macular oedema, 33,34 however their use is not routine in most departments and some express concern with using multiple drops and the risks of drop toxicity. Some ophthalmologists add topical NSAIDs post-operatively for patients deemed to be more at risk of macular oedema, such as those with diabetic retinopathy but no consensus exists in terms of their use.…”
Section: Cystoid Macular Oedemamentioning
confidence: 99%
“…Prospective studies evaluated the effect of a postoperative NSAID on the development of macular oedema after phacoemulsification. 7,[17][18][19] At 5 weeks after phacoemulsification, Miyake's study documented 5.7 vs 54.7% angiographic CME in the eyes that received only diclofenac 0.1% vs the eyes that received only flurometholone 0.1%, respectively. 7 Two recent studies confirmed these findings when an NSAID was used preoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 99%